3D cloud modeling base on fractal particle method - Helin Cui; Min Qi; Dajian Li (2011 International Conference on Electrical and Control Engineering, 2011)
The cloud modeling is universal used in many virtual reality systems. For the simulation of natural landscape, the cloud modeling technique has important influence on the scene's realistic effect. After analyzing the application of cloud modeling methods used in recent years, this article proposes a new method used to cloud modeling, Fractal Particle Method, which constructed with the combination of particle system and fractal algorithm rendering with smoke effect to render vividly. According to the simulating result demonstration, we obtain the dynamic 3D cloud model with significant visual effect used in a real-time visual simulation system.